Study of Evolution of Framework’s for Measuring Economic Empowerment of Women - MEHTA, MS SHIVANI; BHATTACHARJEE, DR MAHUA (The journal of contemporary issues in business and government, 2021)
Literature circling around empowerment of women has been extensively studied to craft some significant methodological stand about the measurement of empowerment (Kabeer 2002).There is increasing acknowledgement that economically empowering women is vital both to gain women’s rights and to achieve wider development goals such as economic growth, education, poverty reduction, health, and welfare. This study therefore focuses on understanding the evolution of concept on women empowerment over the years and its importance. Alongside the changed definition of women empowerment, it extensively studies the various frameworks extended for measuring women’s economic empowerment. Finally, it concludes by deducing the major constructs or indictors that pay a pivotal role in measuring economic empowerment of women. It is through measurement of these constructs that effective policy can be formulated for effectively empowering women globally.